Few-Mode Erbium-Doped Fiber with Three-Layer Center-Recessed Doping for Gain Equalization - Shengchen Bao; Yu Cheng; Yi Tang; Ming Chen; Shijie Deng; Libo Yuan (Sensors)
We propose a design method for few-mode erbium-doped fiber (FM-EDF) incorporating stratified doping. In the simulation design, the FM-EDF effectively reduces the differential mode gain (DMG) through the utilization of stratified doping. Simulations indicate that at an input signal power of −30 dBm, the designed fiber achieves a DMG of less than 0.5 dB across five spatial modes spanning the entire C-band (1530–1570 nm) and exceeds 20 dB gain within the range of 1530–1560 nm. Additionally, experiments using unidirectional pumping demonstrate that the FM-EDF achieves full-band gain greater than 20 dB, with a maximum gain approaching 30 dB and DMG <1 dB, across the C-band in three spatial modes. In summary, the proposed FM-EDF enhances the efficiency and reliability of long-distance signal transmission in optical communication networks, making it suitable for high-capacity optical fiber communication systems as well as long-distance sensing systems.